Implementation of the Routine Counselling Program Communication in Addressing Student Mental Health Issues at SMP Tri Guna Bhakti Surabaya - Yufrida Nirwagiasih; Ayu Erni Jusnita; Zulaikha Zulaikha (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to explore the implementation of communication within routine counselling programmes as an intervention strategy to address student mental health issues at SMP Tri Guna Bhakti Surabaya. The investigation focuses on three primary problems: broken home backgrounds, lack of parental attention, and economic limitations. This research employed a qualitative descriptive approach, collecting data through in-depth interviews, participatory observation, and documentary studies involving school counsellors, teachers, students, and parents. Grounded in Interpersonal Communication Theory and Therapeutic Communication Theory, the analysis reveals that routine counselling programmes serve as a vital communication platform enabling empathetic, open dialogue between counsellors and students experiencing psychological distress. Key findings indicate that effective counselling communication requires consistent trust-building, active listening, and culturally sensitive message delivery tailored to each student’s unique circumstances. However, the study identifies significant systemic barriers, including student reluctance to disclose personal problems due to social stigma, limited counsellor availability, and insufficient parental engagement in follow-up communication. Despite these critical challenges, the implementation of the programme demonstrates substantial positive outcomes, including reduced student anxiety, improved academic motivation, and fostered psychological resilience. The study concludes that integrating structured interpersonal and therapeutic communication strategies within school counselling frameworks is essential for creating supportive, inclusive educational environments. These strategies are crucial to effectively address the multifaceted, urgent mental health needs of adolescents from vulnerable socioeconomic backgrounds, providing a scalable model for similar urban educational institutions.